Modulation of catalytic activity of BSCF towards electrochemical oxygen reactions using different synthetic approaches - Bhagat S.; Singh N.; Singh M.; Singh A.K.; Singh S.; Azad U.P.; Singh A.K. (My University, 2025)
This study is focused on the synthesis of the perovskite oxide materials, particularly Ba0.5Sr0.5Co0.8Fe0.2O3-δ, using different synthetic approaches (sol-gel and co-precipitation techniques) and different complexing agents and fuels and their applications for electrochemical water splitting and fuel cells. Prepared perovskite oxide materials exhibits dual catalytic behaviour as it shows the catalytic activity toward the oxygen evolution and reduction reactions in alkaline solution. The Ba0.5Sr0.5Co0.8Fe0.2O3-δ electrocatalyst exhibits remarkable efficiency and durability for the OER in basic electrolytes, with a Tafel slope of 70.38 mV/dec for Best catalyst. The best ORR activity observed for Ba0.5Sr0.5Co0.8Fe0.2O3-δ synthesized using citric acid shows Tafel slope of 356.43 mV/dec. These oxide materials also show enhanced efficiency in capacitive applications. Additionally, the prepared perovskite oxide materials have been characterized by Powder X-ray diffraction, Le-Bail refinement, scanning electron microscopy, Energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy analysis, and high-resolution Transmission Electron Microscopy. Electrochemical techniques such as linear sweep voltammetry, cyclic voltammetry, and electrochemical impedance spectroscopy techniques were used to assess the catalytic performance of the prepared electrocatalysts in 0.1M KOH solution. © 2024 Hydrogen Energy Publications LLC